SISTEM PAKAR DIAGNOSIS TINGKAT KECEMASAN MAHASISWA DALAM PENYUSUNAN SKRIPSI MENGGUNAKAN METODE CERTAINTY FACTOR - Maria Louise Ludgardis Muku; Sebastianus A S Mola; Meiton Boru; Nelci D Rumlaklak; Tiwuk Widiastuti (J-ICON : Jurnal Komputer dan Informatika, 2022)
The level of student anxiety when compiling a thesis impacts the length of the lecture process. The number of clinical psychologists not proportional to the number of students in East Nusa Tenggara causes many students not to consult a psychologist. An expert system for diagnosing student anxiety levels using the certainty factor method with a HARS scale for 14 criteria and 81 symptoms will help students analyze their anxiety levels. The results of the study based on 300 student data obtained that the accuracy of the expert and system results was 100%, where the more extended the study period, the higher the level of anxiety in students.